DOI: 10.17077/etd.53wnjugw
|View full text |Cite
|
Sign up to set email alerts
|

Screening for cervical cancer

Abstract: Cervical cancer is the single most common cancer in India, affecting an estimated 134,420 women in 2008. With access to early detection and basic treatments, most cases of cervical cancer are preventable. Moreover, if treatment is administered during the earliest stages of cervical cancer, 5-year survival rates can be increased to higher than 90 percent. Unfortunately, despite the availability of methods for prevention, more than 95 percent of women in India have never been screened for cervical cancer. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 100 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…Previous studies have reported similar findings. 29 , 30 , 52 This study further revealed that 97% of the respondents could not afford the cost of Pap smears as it is not covered by the National Health Insurance Scheme.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous studies have reported similar findings. 29 , 30 , 52 This study further revealed that 97% of the respondents could not afford the cost of Pap smears as it is not covered by the National Health Insurance Scheme.…”
Section: Discussionmentioning
confidence: 81%
“…Opportunistic screening in health facilities could be encouraged to improve screening uptake, especially in women within the lower socioeconomic groups. 13 30 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found cost of cervical cancer screening to be a critical barrier to screening [ 50 53 ], if women perceived the cost to be high. One previous study reported that women may be willing to have cervical cancer screening if employers pay for the cost of screening [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Screening is defined as “the systematic application of a test or an inquiry to identify individuals at sufficient risk of a specific disorder to warrant further investigation or direct preventive action among persons who have not sought medical attention on account of symptoms of that disorder [ 10 ]. On the other hand, screening uptake refers to the proportion of persons eligible to be screened within a population who have been both invited for screening and have received an adequate screening during a specified period [ 11 ]. Experience from the developed world shows that effective population-based screening programmes can easily reduce the incidence of cervical and breast cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Employed females are more inclined to go for screening because of their higher opportunity cost, higher incomes, and ability to afford out-of-pocket expenditure [ 16 ]. On the other hand, rural women are less likely than urban women to go for cervical and breast screening [ 11 , 17 , 18 ]. Studies of breast and cervical screening show that women with greater access to health care, such as those with health insurance, are opting to have screening tests [ 16 , 19 ].…”
Section: Introductionmentioning
confidence: 99%